Analisis Tingkat Literasi Data di Kalangan Pustakawan Badan Riset dan Inovasi Nasional - Noeraida Noeraida; Rochani Nani Rahayu; Agus Rifai (Media Pustakawan, 2022)
Based on Law Number 11 of 2019 concerning the National System of Science and Technology chapter 40 regulating the mandatory handover of primary data for the output of research, it is necessary to measure the level of data literacy among librarians of the National Research and Innovation Agency (BRIN). As a newly formed institution, BRIN requires a reference for the leadership in implementing the law. This study aims to determine the level of data literacy among librarians based on agency origin, education, age, gender, years of service, and level of position. The method used is a survey of 68 respondents from Ex BATAN, BPPT, LIPI, and LAPAN. The indicators consist of data culture, searching, visualizing, communicating, assessing & interpreting data. Data processing used SPSS 26 and Lickert scale. The result of this study is that in general, the level of data literacy of BRIN librarians was in a good category. The level of data literacy of BPPT librarians is in the first position, the librarian with undergraduate education level has the highest scores. Women are more literate than men. Librarians with 10-15 years of service entered the first position. Librarians aged more than 60 years and the main expert librarian were ranked first. This study concludes that the level of data literacy in BRIN librarians is in a good category. However, data visualization and communication are in the sufficient category, so it is recommended to provide capacity building for librarians through training and the like.